One‐step synthesized magnetic MIL‐101(Cr) for effective extraction of triazine herbicides from rice prior to determination by liquid chromatography‐tandem mass spectrometry. Issue 18 (22nd July 2019) - Jiang, Yanxiao; Piao, Huilan; Qin, Zucheng; Li, Xiaolei; Ma, Pinyi; Sun, Ying; Wang, Xinghua; Song, Daqian
Abstract: The magnetic metal‐organic framework MIL‐101(Cr) material‐based solid‐phase extraction method coupled with high‐performance liquid chromatography and tandem mass spectrometry was applied to extract seven triazine herbicides in rices. Fe3 O4 /MIL‐101(Cr) was synthesized using reduction‐precipitation method, in which steps including pre‐synthesis and modification of Fe3 O4 nanoparticles were by‐passed. Various parameters including extraction solvent type and volume, ultrasonic extraction time, amount of Fe3 O4 /MIL‐101(Cr) microspheres, adsorption time, desorption volume and time were investigated. Under optimal conditions, the proposed method had the limit of detection (S/N = 3) and the limit of quantification (S/N = 10) of 1.08–18.10 and 3.60–60.20 pg/g, respectively. Relative standard deviations calculated for all herbicides with concentrations of 2 and 20 ng/g were in the range of 0.5 to 13% (n = 3). In addition, at the two above‐mentioned concentrations, the method achieved relative recoveries percentages of 79.3 to 116.7% when applied to determine the triazine herbicides in real samples spiked. This rapid, green, non‐polluting, pre‐concentrated extraction method was successfully developed and applied to analyze herbicides in rice samples.